Sengketa Hak Paten Dalam Persaingan Bisnis (Studi Kasus Apple vs. Samsung) - Yuhanna Putri Wahyu Ningrum; Romi Faslah (CV. ITTC INDONESIA, 2025)
Patents serve as a crucial legal instrument in promoting innovation and economic growth. By granting exclusive rights to inventors, patents are intended to stimulate creativity and investment in research and development. This study aims to analyze the role of patents in fostering innovation, examine their impact on business competition, and review the regulatory framework governing patent protection in Indonesia. The research employs a descriptive qualitative approach using literature review and secondary data analysis from legal documents, academic journals, and reports from relevant institutions. The findings indicate that patents can provide strong incentives for innovators but may also pose barriers to competition if not accompanied by proper regulation. Indonesia's regulatory framework, particularly Law No. 13 of 2016 on Patents, provides a relatively adequate legal foundation but still faces challenges in terms of enforcement and oversight. The study concludes that a balance between patent protection and market interests is essential to foster a healthy and competitive innovation ecosystem.